Preparation method and application of high-performance solid hydrogen storage material
By growing metal organic frames in situ on biological carbon carriers, a high specific surface area MOFs@pine wood chip composite carbon matrix was prepared, which solved the problems of safety and low storage efficiency in hydrogen solid storage technology, and achieved high hydrogen storage capacity and environmentally friendly hydrogen storage solutions.
Patent Information
- Application Number
- CN202411526892.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing hydrogen solid-state storage technology faces the problems of safety and low storage efficiency. Metal organic frames (MOFs) powder-like crystallization and brittleness limit their application. The adsorption performance of biocarbon materials needs to be improved, and there are challenges in actual applications.
Using a simple and green and environmentally friendly method, metal organic frame crystals are grown in situ on a biological carbon carrier to prepare a high specific surface area MOFs@pine wood chip composite carbon matrix with three-dimensional interconnected pore structure and adjustable pores. Prepare ZIF-8@pine wood chip composite carbon matrix by pickling, carbonization, activation and chemical reaction.
It has achieved rich functional groups, adjustable specific surface area and pore structure, achieved high hydrogen storage capacity, rich material sources, low cost, and easy to prepare on a large scale, providing a new method for green hydrogen storage composite materials, and improving metal organic framework and biogenesis Interface compatibility of material substrates.
Smart Images

Figure CN119263209A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of MOFs@biomass composite carbon matrix preparation, and specifically relates to a preparation method and application of a high-performance solid hydrogen storage material. Background Art
[0002] As an efficient and renewable energy source, hydrogen plays an important role in promoting global sustainable development and achieving the goals of "carbon peak" and "carbon neutrality". However, the low density of hydrogen brings technical challenges to its storage and transportation. At present, hydrogen storage technologies mainly include high-pressure gas storage, liquid storage and solid storage. Among them, solid storage technology has attracted widespread attention due to its safety and storage efficiency.
[0003] Metal-organic frameworks (MOFs) are a new class of porous coordination polymers with highly customizable pore structures and functionalized components. They show great potential in the field of hydrogen storage, especially zeolitic imidazolate frameworks (ZIFs) MOFs, which combine the high porosity of traditional zeolites with the tunable structural advantages of MOFs and show superior performance. However, the powdery crystalline morphology and brittleness of ZIFs limit their widespread use in practical applications.
[0004] Biochar is a material that has been widely used in commercial hydrogen storage. Due to its high specific surface area and porous structure, it can effectively adsorb and release hydrogen at low pressure and ambient temperature. However, the adsorption performance of biochar materials still has room for improvement, and it also faces some challenges in practical applications.
[0005] To overcome the above limitations, it is necessary to propose a method to in situ grow MOF crystals on biocarbon supports. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and application of a high-performance solid-state hydrogen storage material, and to prepare a MOFs@pine sawdust composite carbon matrix with a high specific surface area by a simple process, green environmental protection, and economical and efficient method. The MOFs@pine sawdust composite carbon matrix has a three-dimensional interconnected pore structure and an adjustable specific surface area, and has a high hydrogen storage capacity.
[0007] The technical solution adopted by the present invention is as follows:
[0008] A high-performance solid-state hydrogen storage material, which is a ZIF-8@pine sawdust composite carbon matrix.
[0009] A method for preparing a high-performance solid-state hydrogen storage material, the method for preparing the above-mentioned solid-state hydrogen storage material, the method comprising the following steps:
[0010] S1: The biomass is subjected to acid washing, washed with deionized water until neutral, and then dried for later use;
[0011] S2: Under an inert protective atmosphere, carbonizing the biomass obtained in S1 to obtain a carbon precursor;
[0012] S3: grinding and mixing the carbon precursor obtained in S2 with a chemical activator, and then loading the mixture into a self-made reactor, and sealing the reactor after exhausting all the air in the reactor to perform an activation reaction;
[0013] S4: After the activation reaction is completed under an inert protective atmosphere, the product is taken out, and the carbon material is obtained after acid washing, water washing, and drying;
[0014] S5: re-treating the treated carbon material with an alkaline solution and washing with deionized water until neutral;
[0015] S6: reacting the obtained carbon material with Zn(NO3)2·6H2O and 2-methylimidazole in a methanol solution for 24 h;
[0016] S7: washing with methanol solution and vacuum drying.
[0017] An application of a high-performance solid-state hydrogen storage material, which is used to apply the above-mentioned solid-state hydrogen storage material in the field of hydrogen storage.
[0018] The technical effects achieved by the present invention are:
[0019] The present invention has rich functional groups, adjustable specific surface area and pore structure. At a temperature of 77K and a pressure of 60bar, the hydrogen storage capacity of the MOFs@pine sawdust composite carbon matrix is ≧5.76wt%, which meets the hydrogen storage quality standard of solid hydrogen storage materials stipulated by the U.S. Department of Energy. At the same time, the raw materials used are abundant in source, the process is simple, the cost is low, and it is easy to achieve large-scale preparation, providing new ideas for promoting the scale-up of solid hydrogen storage industry technology;
[0020] And make full use of the waste biomass carbon materials with low density, high porosity and good mechanical stability, providing excellent nucleation conditions for the in-situ growth of metal organic framework crystals. This method makes the metal organic framework and the biomass substrate closely attached through hydrogen bonds and electrostatic interactions, with good interfacial compatibility, thus achieving the successful preparation of metal organic framework @ pine sawdust composite carbon matrix with high specific surface area and three-dimensional multi-level pore structure. In addition, compared with traditional methods, this process is clean and pollution-free, providing a new method for the development of new green hydrogen storage composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the nitrogen isothermal adsorption / analysis test result of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 3 of the present invention;
[0022] Figure 2 This is the pore size distribution test result of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 3 of the present invention;
[0023] Figure 3 This is the XRD test result of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 3 of the present invention;
[0024] Figure 4 is a SEM image of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 3 of the present invention;
[0025] Figure 5 is the XPS general spectrum of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 3 of the present invention;
[0026] Figure 6 The C1s spectrum, O 1s spectrum, N 1s spectrum and Zn 2p spectrum of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 3 of the present invention;
[0027] Figure 7 The hydrogen storage performance test results of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 3 of the present invention at 77K and 0-60bar;
[0028] Figure 8 This is the nitrogen isothermal adsorption / analysis test result of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 4 of the present invention;
[0029] Fig. 9 This is the pore size distribution test result of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 4 of the present invention;
[0030] Fig.10 This is the XRD test result of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 4 of the present invention;
[0031] Fig.11 This is the hydrogen storage performance test result of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 4 of the present invention at 77K and 0-60bar;
[0032] Fig.12 This is the test result of the hydrogen storage performance of the ZIF-8@pine sawdust composite carbon matrix prepared in Example 4 of the present invention at 77K and 0-60bar. DETAILED DESCRIPTION
[0033] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is specifically described below in conjunction with embodiments. It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention.
[0034] Embodiment 1:
[0035] A high-performance solid-state hydrogen storage material, which is a ZIF-8@pine sawdust composite carbon matrix.
[0036] The ZIF-8@pine sawdust composite carbon matrix includes a three-dimensionally interconnected multi-level pore structure, and the specific surface area of the composite carbon matrix is ≥1194.41m 2 ·g -1 , the micropore volume is 0.19-0.44cm 3 ·g -1 At a temperature of 77K and a pressure of 60bar, the hydrogen storage capacity of the MOFs@pine sawdust composite carbon matrix is ≥5.76wt%.
[0037] Embodiment 2:
[0038] A method for preparing a high-performance solid-state hydrogen storage material, the method for preparing the above-mentioned solid-state hydrogen storage material, the method comprising the following steps:
[0039] S1: The biomass is subjected to acid washing, washed with deionized water until neutral, and then dried for later use, and the biomass is pine sawdust;
[0040] S2: Under an inert protective atmosphere, the biomass obtained in S1 is carbonized to obtain a carbon precursor, the carbonization temperature is 500° C., and the carbonization holding time is 120 min;
[0041] S3: grinding and mixing the carbon precursor obtained in S2 with a chemical activator, and then loading the mixture into a self-made reactor, and sealing the reactor after exhausting all the air in the reactor to perform an activation reaction, wherein the chemical activator is any one of KOH or NaOH, and the mass ratio of the chemical activator to the carbon precursor is 1:1;
[0042] S4: After the high-temperature activation reaction is completed under an inert protective atmosphere, the product is taken out, and the carbon material is obtained after acid washing, water washing, and drying. The high-temperature heating temperature in the activation reaction is 800° C., and the high-temperature heating holding time is 120 min. The inert protective atmosphere in S2 and S4 is any one of nitrogen, argon or helium;
[0043] S5: re-treating the treated carbon material with an alkaline solution and washing with deionized water until neutral;
[0044] S6: reacting the obtained carbon material with Zn(NO3)2·6H2O and 2-methylimidazole in a methanol solution for 24 hours, using an in-situ growth method, with a mass ratio of Zn(NO3)2·6H2O to the carbon material of 0.5:1, 1:1 and 2:1;
[0045] S7: washing with methanol solution and vacuum drying.
[0046] The specific preparation example is as follows:
[0047] Embodiment 3:
[0048] The pine sawdust was pickled by adding hydrochloric acid and stirring in a water bath at a constant temperature and magnetic stirring, then washed with water until the pH was neutral and then dried; 5 g of the sample after pickling was weighed for pre-carbonization, heated to 500°C at a heating rate of 5°C / min under a N2 protective atmosphere, and kept warm for 120 minutes, and then naturally cooled to room temperature to obtain a carbon precursor, named PSC;
[0049] Potassium hydroxide and PSC were fully ground and mixed in a mass ratio of 1:1, and then loaded into a homemade reactor for high-temperature heating. They were heated to 800°C in a N2 atmosphere and kept warm for 120 minutes. After cooling naturally to room temperature, the product was taken out, pickled with hydrochloric acid to remove impurities, and then washed with distilled water until the pH was neutral and dried to obtain sawdust-derived biochar named PSB. The obtained PSB was immersed in a 15wt% NaOH aqueous solution and allowed to stand for 1 hour. Stir in the aqueous solution for 24 hours until the pH value of the washing liquid reached 9;
[0050] The PSB that had been pretreated again was homogeneously mixed with different mass ratios of Zn(NO3)2·6H2O (0:1, 0.5:1, 1:1 and 2:1), and 2.4g of Zn(NO3)2·6H2O was dissolved in 25mL of methanol and 3mL of deionized water to form a Zn(NO3)2 solution. The pretreated biomass sample was immersed in this solution for 2h to ensure sufficient exchange of Zn and Na ions. Subsequently, a 2-methylimidazole solution containing 13.2g of 2-methylimidazole in methanol (25mL) and deionized water (3mL) was added to the above solution. Stirring at room temperature for 24h formed the ZIF-8@pine sawdust composite material. After washing with methanol and drying in a vacuum oven at 103°C for 48h, a ZIF-8@pine sawdust composite carbon matrix was obtained. The sample was named ZIF-8@PSX-Y, where X represents the treatment method of the biomass material (original, carbonized and activated), and Y represents the mass ratio of Zn(NO3)2·6H2O to pine sawdust. All embodiments used the Brunauer-Emmett-Teller (BET) method to calculate the specific surface area of the sample, and the non-local density functional theory (NLDFT) was used to analyze its pore size distribution. The total pore volume was determined by the nitrogen absorption at the relative pressure P / P0=0.99. The specific surface area and pore volume of the composite carbon matrix were determined using the BET method;
[0051] Figure 1The nitrogen isothermal adsorption / desorption curve of the composite carbon matrix material prepared above. As can be seen from the figure, the isotherm type of all samples is VI type, indicating that the composite carbon matrix not only has a rich microporous structure, but also has a certain amount of mesoporous structure. After activation treatment, the specific surface area of the sample PSB increased significantly (S BET =544.45m 2 ·g -1 The specific surface area of ZIF-8@PSB-X composite material increased from 625.75 to 1199.41 m 2 ·g -1 The micropore specific surface area reaches 1037.51m 2 ·g -1 , accounting for 86.50% of the total specific surface area. Figure 2 The pore size distribution of the composite carbon matrix material prepared above shows that the pore size distribution of all samples is mainly below 5 nm, with a wide pore distribution range and a multi-level pore distribution, containing a large number of micropore structures around 0.6 to 2 nm. The micropore volumes of PSB, ZIF-8@PSB-0.5, ZIF-8@PSB-1 and ZIF-8@PSB-2 are 0.19, 0.26, 0.34 and 0.44 cm 3 ·g -1 . As the ZIF-8 content increases, the composite carbon matrix shows a richer microporous structure;
[0052] It is worth noting that the pore size of the ZIF-8@PSB composite material is mainly distributed in the range of 2 to 4 nm, indicating that the composite carbon matrix also has small-sized mesopores. Figure 3 XRD pattern of the composite carbon matrix prepared above. The diffraction peaks of the ZIF-8@PSB-X composite carbon matrix completely match the standard spectrum of ZIF-8 crystals, clearly showing that the ZIF-8 crystal particles have successfully grown in the pine sawdust matrix. The characteristic peaks of the pine sawdust composite material observed in the XRD spectrum are located at 2θ=7.3°, 10.4°, 12.9°, 14.8° and 18.1°, corresponding to the (100), (200), (211), (220) and (222) crystal planes of ZIF-8 crystals. These peaks are consistent with the data in the ZIF-8 standard card JCPDS 00-062-1030, and are consistent with the experimentally measured XRD data;
[0053] Figure 4 a. Figure 4 b. Figure 4 c and Figure 4 d is the SEM image of sample ZIF-8@PSB-X at different magnifications. It can be seen from the figure that the prepared activated carbon material has a three-dimensional cubic structure with a well-developed pore structure, which is also one of the reasons for its high specific surface area. Figure 5XPS overall spectrum of sample ZIF-8@PSB-X. Figure 6 The C1s spectrum, O 1s spectrum, N 1s spectrum and Zn 2p spectrum of sample ZIF-8@PSB-X are shown in Figure 2. Figure 6 It can be seen that the sample contains four elements: C, N, O, and Zn, and is mainly composed of C. The C 1s spectrum is convolved into three features, corresponding to 284.8 eV (CC), 286.2 eV (CO / CN), and 288.9 eV (OC=O), respectively. The O 1s spectrum is convolved into three features, corresponding to 532.3 eV (CO), 533.6 eV (OC=O), and 535.8 eV (OH), respectively. The N 1s spectrum is convolved into three features, corresponding to 397.8 eV (N-6), 400.5 eV (N-5), and 401.5 eV (N-Ox), respectively. The Zn 2p spectrum is convolved into two features, corresponding to 1022 eV (Zn 2p 3 / 2 ) and 1045eV(Zn 2p 1 / 2 );
[0054] It can be seen that the prepared composite carbon matrix material has rich functional groups. Figure 7 The hydrogen absorption test curve of the composite carbon matrix material prepared above at 77K and 0-60bar is shown in the figure. As can be seen from the figure, the hydrogen absorption amount of ZIF-8@PSB-0 to ZIF-8@PSB-2 gradually increases with the increase of pressure at 77K. When the pressure is 60bar, the hydrogen storage capacity can reach 5.76wt%. In summary, ZIF-8@PSB-2 is preferred as the best MOFs@pine sawdust composite carbon matrix mass ratio.
[0055]
[0056] The above table is Table 1, which is the SSA and pore structure characteristic parameters of PSB and ZIF-8@PSB composite carbon matrix;
[0057] Embodiment 4:
[0058] Similar to the above-mentioned Example 3, this example is another preparation method, as follows:
[0059] The pine sawdust was pickled by adding hydrochloric acid to the water bath with constant temperature magnetic stirring, then washed with water until the pH was neutral and then dried; 5g of the sample after pickling treatment was weighed for pre-carbonization, heated to 500℃ at a heating rate of 5℃ / min under N2 protective atmosphere, and kept warm for 120min, and then naturally cooled to room temperature to obtain a carbon precursor, named PSC; potassium hydroxide and PSC were fully ground and mixed in a mass ratio of 1:1, and then loaded into a homemade reactor for high-temperature heating, heated to 800℃ under N2 atmosphere, kept warm for 120min, and cooled naturally to room temperature, the product was taken out, pickled and impurized with hydrochloric acid, and then washed with distilled water until the pH was neutral and dried to obtain sawdust-derived biochar named PSB. PS, PSC and PSB were immersed in 15wt% NaOH aqueous solution respectively and left to stand for 1h;
[0060] Stir in the aqueous solution for 24 h until the pH value of the washing solution is 9. PS, PSC and PSB that have been pretreated again are homogeneously mixed with different mass ratios of Zn(NO3)2·6H2O (2:1), and 2.4 g of Zn(NO3)2·6H2O is dissolved in 25 mL of methanol and 3 mL of deionized water to form a Zn(NO3)2 solution. The pretreated biomass sample is immersed in this solution for 2 h to ensure sufficient exchange of Zn and Na ions;
[0061] Subsequently, a 2-methylimidazole solution containing methanol (25 mL) and deionized water (3 mL) containing 13.2 g of 2-methylimidazole was added to the above solution. Stirring at room temperature for 24 hours, a ZIF-8@pine sawdust composite material was formed. After washing with methanol and drying in a vacuum oven at 103°C for 48 hours, a ZIF-8@pine sawdust composite carbon matrix was obtained. The samples were named ZIF-8@PS-Y-2 and ZIF-8@PSC-2, where X represents the treatment method of the biomass material (original, carbonized and activated), and Y represents the mass ratio of Zn(NO3)2·6H2O to pine sawdust. All embodiments used the Brunauer-Emmett-Teller (BET) method to calculate the specific surface area of the sample, and the non-local density functional theory (NLDFT) was used to analyze its pore size distribution. The total pore volume was determined by the nitrogen absorption at the relative pressure P / P0=0.99. The specific surface area and pore volume of the composite carbon matrix were determined by the BET method;
[0062] Figure 8 The nitrogen isothermal adsorption / desorption curves of the composite carbon matrix materials prepared above are shown in Figure 1. As can be seen from the figure, the isotherm type of all samples is VI type, indicating that the composite carbon matrix not only has a rich microporous structure, but also has a certain amount of mesoporous structure. After activation treatment, the specific surface area of samples PS and PSC is 26.86 m 2 ·g -1The specific surface area of ZIF-8@PS-X composite material increased from 71.54 to 145.02 m 2 ·g -1 The micropore specific surface area reaches 125.45m 2 ·g -1 , accounting for 86.50% of the total specific surface area. The specific surface area of ZIF-8@PSC-X composite material increased from 85.40 to 472.02 m 2 ·g -1 The micropore specific surface area reaches 435.94m 2 ·g -1 , accounting for 92.4% of the total specific surface area;
[0063] Fig. 9 The pore size distribution of the composite carbon matrix material prepared above shows that the pore size distribution of all samples is mainly below 10 nm, with a wide pore distribution range and a multi-level pore distribution, containing a large number of micropore structures around 0.6 to 2 nm. The micropore volumes of PS, ZIF-8@PS-0.5, ZIF-8@PS-1 and ZIF-8@PS-2 are 0.01, 0.05, 0.06 and 0.07 cm 3 ·g -1 The micropore volumes of PSC, ZIF-8@PSC-0.5, ZIF-8@PSC-1 and ZIF-8@PSC-2 are 0.04, 0.14, 0.17 and 0.30 cm 3 ·g -1 . As the content of ZIF-8 increases, the composite carbon matrix shows a richer microporous structure. It is worth noting that the pore size of the ZIF-8@PSB composite material is mainly distributed in the range of 2 to 10 nm, indicating that the composite carbon matrix also has small-sized mesopores;
[0064] Fig.10 XRD pattern of the composite carbon matrix prepared above. The diffraction peaks of the ZIF-8@PS-X and ZIF-8@PSC-X composite carbon matrices are completely matched with the standard spectrum of ZIF-8 crystals, which clearly shows that the ZIF-8 crystal particles have been successfully grown in the pine sawdust matrix. The characteristic peaks of the pine sawdust composite material observed in the XRD spectrum are located at 2θ=7.3°, 10.4°, 12.9°, 14.8° and 18.1°, corresponding to the (100), (200), (211), (220) and (222) crystal planes of ZIF-8 crystals. These peaks are consistent with the data in the ZIF-8 standard card JCPDS 00-062-1030, and are consistent with the experimentally measured XRD data;
[0065] It can be seen that the prepared composite carbon matrix material has rich functional groups. Fig.11 and Fig.12The hydrogen absorption test curve of the composite carbon matrix material prepared above at 77K and 0-60bar. It can be seen from the figure that the hydrogen absorption amount of ZIF-8@PS-0 to ZIF-8@PS-2 gradually increases with the increase of pressure at 77K. When the pressure is 60bar, the hydrogen storage capacity can reach 2.08wt%. Among the PSC series materials, the hydrogen storage capacity of the ZIF-8@PSC-2 composite carbon matrix is as high as 3.15wt%. And among the PSB series materials, the hydrogen storage capacity of the ZIF-8@PSB-2 composite carbon matrix is as high as 5.76wt%;
[0066] In summary, ZIF-8@PSB-2 was selected as the best MOFs@pine sawdust composite carbon matrix treatment condition.
[0067]
[0068] The above table is Table 2, which is the SSA and pore structure characteristic parameters of PS, PSC, PSB and ZIF-8@PS, ZIF-8@PSC, ZIF-8@PSB composite carbon matrix;
[0069] Embodiment 5:
[0070] An application of a high-performance solid-state hydrogen storage material, which is used to apply the solid-state hydrogen storage material in the field of hydrogen storage.
[0071] ZIF-8@pine sawdust shows great potential in the field of hydrogen storage. ZIF-8 material has a high specific surface area and porous structure, which enables it to effectively adsorb and store hydrogen at low temperatures. By combining ZIF-8 with pine sawdust, its mechanical strength and stability can be further improved;
[0072] In practical applications, ZIF-8@pine sawdust can be used in hydrogen storage devices, and through its porous structure and high adsorption capacity, it can achieve efficient hydrogen storage under low temperature and high pressure conditions. This material can not only increase the hydrogen storage capacity, but also maintain stable performance during multiple cycles.
[0073] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to the conventional means in the art unless otherwise specified and limited.
Claims
1. A high-performance solid-state hydrogen storage material, characterized in that: The solid-state hydrogen storage material is a ZIF-8@pine sawdust composite carbon matrix.
2. The solid hydrogen storage material according to claim 1, characterized in that: The ZIF-8@pine sawdust composite carbon matrix includes a three-dimensionally interconnected multi-level pore structure, and the specific surface area of the composite carbon matrix is ≥1194.41m 2 ·g -1 , the micropore volume is 0.19-0.44cm 3 ·g -1 .
3. A method for preparing a high-performance solid hydrogen storage material, characterized in that: The preparation method is used to prepare the solid hydrogen storage material according to any one of claims 1 to 2, and the preparation method comprises the following steps: S1: The biomass is subjected to acid washing, washed with deionized water until neutral, and then dried for later use; S2: Under an inert protective atmosphere, carbonizing the biomass obtained in S1 to obtain a carbon precursor; S3: grinding and mixing the carbon precursor obtained in S2 with a chemical activator, and then loading the mixture into a self-made reactor, and sealing the reactor after exhausting all the air in the reactor to perform an activation reaction; S4: After the activation reaction is completed under an inert protective atmosphere, the product is taken out, and the carbon material is obtained after acid washing, water washing, and drying; S5: re-treating the treated carbon material with an alkaline solution and washing with deionized water until neutral; S6: reacting the obtained carbon material with Zn(NO3)2·6H2O and 2-methylimidazole in a methanol solution for 24 h; S7: washing with methanol solution and vacuum drying.
4. The preparation method according to claim 3, characterized in that: The biomass in S1 is pine sawdust.
5. The preparation method according to claim 3, characterized in that: The carbonization temperature in S2 is 500° C., and the carbonization holding time is 120 min.
6. The preparation method according to claim 3, characterized in that: The chemical activator in S3 is any one of KOH and NaOH, and the mass ratio of the chemical activator to the carbon precursor is 1:
1.
7. The preparation method according to claim 3, characterized in that: The temperature in the S4 activation reaction is 800° C. and the insulation time is 120 min.
8. The preparation method according to claim 3, characterized in that: The inert protective atmosphere in S2 and S4 is any one of nitrogen, argon or helium.
9. Application of a high-performance solid-state hydrogen storage material, characterized in that: The application is used for applying the solid-state hydrogen storage material described in any one of claims 1 to 2 in the field of hydrogen storage.
Citation Information
Cited By
Bimetal MOF / activated carbon composite material as well as preparation method and application thereof
CN121107354A
Carbon-based fuel micro-nano structure cascade hot sequence construction enhanced hydrogen storage method
CN122324752A